Administration of Chinpi, a Component of the Herbal Medicine Ninjin-Youei-To, Reverses Age-Induced Demyelination. (5th June 2011) - Sato, Nanako; Seiwa, Chika; Uruse, Michihiro; Yamamoto, Masahiro; Tanaka, Kayoko; Kawakita, Takuya; Komatsu, Yasuhiro; Yasukawa, Akio; Takao, Masakatsu; Kudo, Chiaki; Hasegawa, Atsuhiko; Ishige, Atushi; et al.
Abstract : The disruption of myelin causes severe neurological diseases. An understanding of the mechanism of myelination and remyelination is essential for the development of therapeutic strategies for demyelination diseases. Our previous findings indicated that the FcRγ/Fyn cascade is a potential therapeutic target for remyelination caused by the Chinese/Japanese traditional herbal (Kampo) medicine ninjin'youeito (Ninjin-youei-to, NYT), which is a hot-water extract made from 12 medicinal herbs. To identify which constituents of NYT are involved in the reversal of demyelination and to examine the potential therapeutic effect, we tested several of the chemical constituents of NYT. Here, we report that Chinpi, a constituent of NYT, upregulates the FcRγ/Fyn signaling cascade resulting in a potentially therapeutic effect against age-induced demyelination. In addition, we observed that phosphorylated (activated) FcRγ/Fyn upregulated the expression of the 21.5 kDa isoform of myelin basic protein, inducing rapid morphological differentiation, when oligodendrocyte precursor cells (OPCs) were cultured in the presence of hesperidin and/or narirutin (the major active constituents of Chinpi). These results suggest that hesperidin and narirutin participate in the FcRγ/Fyn signaling pathway in OPCs causing these cells to differentiate into myelinating oligodendrocytes.